Church Accounting Concepts with the Understanding of God's Kingdom - Anita Nisa Kambey (International Journal of Religious and Cultural Studies, 2021)
The purpose of this article is to present the concept of church accounting with an understanding of the Kingdom of God. The construction employed is the interrelation between agency theory, entity theory and 'the sacred and divide' thought of Robert Laughin. Indonesian accounting standard for Non-Profit organization (PSAK No. 45) is not taken into consideration in this church accounting because it has elements of secularism that are not in line with the ecclesiastical principle of sacredness. Recommendations of Booth and Laughlin which were then modified without eliminating essential assumptions and referring to the Bible as a normative source, are adjusted to the current church accounting practice. The theory of cognitive psychology proposed by Robert Sternberg was employed in the reconstruction. Church accounting that focuses on God, not only on material matters, can be reconstructed. Further, it is necessary to deconstruct the psychology of leaders and congregations.